Insights into cardiac alterations after pre‐eclampsia: an echocardiographic study. (5th January 2017) - Orabona, R.; Vizzardi, E.; Sciatti, E.; Bonadei, I.; Valcamonico, A.; Metra, M.; Frusca, T.
ABSTRACT: Objectives: To investigate cardiovascular (CV) performance status several years after early‐onset (EO) or late‐onset (LO) pre‐eclampsia (PE), using echocardiography to assess myocardial strain and left ventricular (LV) torsional mechanics and ventricular–arterial coupling (VAC). Methods: Thirty non‐pregnant women with a previous singleton pregnancy complicated by EO‐PE, 30 who had experienced LO‐PE and 30 controls underwent echocardiography with two‐dimensional (2D) speckle tracking between 6 months and 4 years after delivery and their findings were compared. All women were free from CV risk factors. VAC was defined as the ratio between aortic elastance (Ea) and LV end‐systolic elastance (Ees). Results: Women in the EO‐PE group showed a persistent subclinical impairment in LV systole and a slight alteration in right ventricular function, with reductions in LV 2D strain (circumferential, radial and longitudinal) and right ventricular 2D strain and impairment of LV torsional mechanics, when compared both with women in the LO‐PE group and with healthy controls. Although VAC was within the normal range in the whole study cohort, its individual components Ea and Ees were significantly altered more often in the EO‐PE group than in both the LO‐PE group and controls. All parameters investigated (except right ventricular 2D strain) were associated independently with gestational age at the time of diagnosis of PE. Conclusions: Women with a history of EO‐PE are more likely to have subclinical impairment of systolic biventricular function than are those with a history of LO‐PE and controls. The components of VAC (Ea and Ees) show subclinical alterations which are more significant in women with a history of EO‐PE than in those with a history of LO‐PE and controls, although VAC itself is maintained. Our study supports the use of closer CV monitoring in previously pre‐eclamptic women, particularly those in whom PE was preterm. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.